Avaliação de estratégias adesivas em lesões cervicais através de revisões sistemáticas e meta-análise - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
Objectives: To compare the retention rates of 1-step self-etch adhesives (1SE) and 3-step etchand- rinse adhesives in non-carious cervical lesions (NCCLs) (1), to assess which adhesive strategy is most effective clinically in NCCLs (2) e whether there are differences in retention rates for OptiBond FL and Clearfil SE Bond adhesives with other adhesive brands (3). Material and Methods: For this study, 3 systematic reviews (SRs) were carried out, and the study (2) was an SR conducted by the mixed treatment comparison methodology (MTC). Only randomized clinical trials (RCTs) in NCCLs according to the eligibility criteria were included. The controlled vocabulary and keywords were combined in the search strategy for PubMed/Medline and adapted to other databases as well as gray literature screening. The risk of bias was assessed using the Cochrane Collaboration tool (RoB) and the heterogeneity was assessed by Cochrane’s Q test and I2 statistics. The GRADE approach was used to assess the quality of evidence. Meta-analysis were conducted for retention rates, marginal discoloration and marginal integrity, at 12 to 24-month, 24 to 36-month and 60-month follow-up periods in the study (1) and in the study (3) meta-analysis for retention rates for OptiBond FL adhesive at 12 to 24-month, 36 to 48-month, 60 to 96-month, 108 to 156-month periods and for the Clearfil SE Bond adhesive at 12 to 24-month and 36 to 48-month.In the study (2), pairwise metaanalysis and Bayesian network meta-analysis were performed for retention rates at 12 to 24- month, 36 to 48-month, over 48-month and the adhesive strategies were rated by SUCRA. Results: In the study (1), no significant differences were observed in retention rates between 1SE adhesives vs 3ER adhesives in the different follow-up periods 12 to 24-month 12 to 24- month (p = 0.66), 24 to 36-month (p = 0.21 ) and 60-month (p = 0.96). A significant difference was found in marginal integrity at 12 to 24-month (p = 0.04) and in marginal discoloration at 12 to 24-month (p = 0.003). In the MTC (2) a significant difference was found in the network result only in the pair 2SE vs 3ER in favor of the strategy 2SE in 12 to 24-month (RR = 0.72; 95% CrI 0.52 to 0.99), in the other periods no significant differences were found. In study (3) no difference was observed for retention rates in the periods of 12 to 24-month (p = 0.97), 36 to 48-month (p = 0.72) and 108 to 156-month (p = 0.73) for OptiBond FL and 12 to 24-month (p = 0.10) and 36 to 48-month (p = 0.17) for Clearfil SE Bond. A significant difference was found for OptiBond FL at 60 to 96-month (p = 0.02), but only 3 studies were included in this meta-analysis. Conclusions: There is no evidence that 3ER adhesives have better retention rates than 1SE adhesives in LCNCs (1). No adhesive strategy was superior to another (2) and there is no evidence that the retention rates of OptiBond FL and Clearfil SE Bond adhesives are higher than those of the adhesive brands with which they were compared (3).
Keywords: Agentes de união à dentina; Lesões cervicais; Eficácia do tratamento.; Revisão sistemática; Meta-análise em rede.; Dentin-bonding agents; Cervical lessions; Clinical efectiveness; Systematic review; Net-work meta-analysis; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA